2020
DOI: 10.1007/s00192-020-04607-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a subsequent pregnancy on anal sphincter integrity and function after obstetric anal sphincter injury (OASI)

Abstract: Introduction and hypothesis Endoanal ultrasound (EAUS) and anal manometry are used in the assessment women with a history of obstetric anal sphincter injury (OASI), both postpartum and in a subsequent pregnancy, to aid counselling regarding mode of delivery (MOD). Methods A prospective observational study between 2012 to 2020 was completed. Women were reviewed 3 months postpartum following OASI and in the second half of a subsequent pregnancy. Anorectal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Presence of defects on EAUS are associated with development of AI symptoms and supported by a strong evidence base within the literature 18 . Abnormal AM has been identified in symptomatic women with OASI and is associated with the presence of defects on EAUS 19,20 . The distinct role of AM in OASI follow‐up has previously been explored by the authors 21 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Presence of defects on EAUS are associated with development of AI symptoms and supported by a strong evidence base within the literature 18 . Abnormal AM has been identified in symptomatic women with OASI and is associated with the presence of defects on EAUS 19,20 . The distinct role of AM in OASI follow‐up has previously been explored by the authors 21 …”
Section: Discussionmentioning
confidence: 84%
“…18 Abnormal AM has been identified in symptomatic women with OASI and is associated with the presence of defects on EAUS. 19,20 The distinct role of AM in OASI follow-up has previously been explored by the authors. 21 Our study identified that 66.3% (n = 894) of women in our tertiary unit were asymptomatic at 6 months following primary OASI repair.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reporting the results of 3D‐EAUS ≥ 3 months after the primary repair of OASI have had rather varying frequencies of defects. For example, Gold et al reported a frequency of 55%, with no endosonographic evidence of tears in 31%, 28 Okeahialam et al found a defect of >1 h (>30° angle) in 32%, 29 and Cerro et al described defects in 90% and found that the extent of a residual anal sphincter defect on 3D‐EAUS was the most relevant factor correlating with symptoms of anal incontinence 15 . Similarly, using transperineal ultrasound (TPUS), Hubka et al reported a defect prevalence of 13.6% in patients diagnosed with OASI, and Shek et al found defects in 40% of patients and associated them with significant symptoms of anal incontinence 16,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Dietz and Shek acknowledge that they failed to validate the 30 • criterion for significant defect using TPUS. We have shown previously using EAUS that, in the immediate postnatal period and in a subsequent pregnancy, anal incontinence symptoms and anal manometry (which correlate with anal sphincter function) are significantly worse in women with an anal sphincter defect > 30 • in comparison to those with smaller defects 6 . Moreover, we found that, in comparison to TPUS, EAUS has the strongest association with anal incontinence symptoms up to 2 years following OASI 7 .…”
mentioning
confidence: 90%